Trans-atrial, Trans-pulmonary Repair of Tetralogy of Fallot in Older Children and Adults: - Koirala, B; Koirala, R; Sharma, J; Pradhan, S; Acharya, A; Sharma, P; Rai, K (Nepalese Heart Journal, 2004)
Tetralogy of Fallot is the most common cyanotic congenital heart disease and has an favorable outcome if dealt with in time. Here we present the retrospective study of immediate outcome of surgical repair of Fallot's Tetralogy carried out at Shahid Gangalal National Heart Centre, Kathmandu, Nepal.